Estudo da implantação da curricularização da extensão no Curso de Direito da Universidade Vale do Acaraú segundo o modelo de currículo da Resolução nº 7/2018 do Conselho Nacional de Educação - Loiola, Alana Vanessa Paulino (2024)
Extension curricularization is a process that aims to integrate extension activities into the curriculum of undergraduate courses, promoting a more organic relationship between teaching, research and extension in higher education institutions, as one of the pillars of academic training and assuming a fundamental role in the exchange of interaction between the university and the community. Through this process, the aim is to strengthen interaction and guarantee the training of professionals engaged with social demands, aware of their transformative role in society. The implementation of extension curricularization in higher education institutions presents several challenges, such as the lack of adequate infrastructure, the culture of devaluing extension activities and the resistance of students who do not recognize the importance of this practice for their training. Furthermore, Resolution No. 07/2018 of the CNE, which establishes guidelines for the implementation of extension curricularization in federal and state universities in the country, is still little known and innovative in a heterogeneous way in the institutions. Under this circumstance, this study seeks to analyze the steps involved in the process of implementing the extension curricularization in the law course at Universidade Vale do Acaraú in accordance with the requirements of Resolution No. 7/2018. Specifically, it is intended to: 1) examine university management and extension curricularization in the context of the new guidelines of Resolution No. 07/2018; 2) identify the procedures and mechanisms for evaluating the curricularization of extension in the UVA Law course, according to the guidelines of the National Education Plan and Resolution nº 07/2018; 3) investigate the perception of managers involved in the extension curricularization process in the UVA Law course; and 4) propose a protocol for self-evaluation and monitoring of extension curricularization as a public policy. To achieve the research objectives, the hypothetical-deductive method will be adopted. As for the approach, qualitative will be used, based on documentary analysis and narrative interviews with managers involved in the process of implementing the curricularization of the extension of the Law course at UVA. The data will be collected from institutional documents, such as teaching plans and the course's pedagogical project, and will be analyzed using the content analysis technique. Thus, contributing to the understanding of the effects of this process in the context of Resolution No. 07/2018, and providing subsidies for the improvement of university extension policies at UVA and for the promotion of a more integrated academic training committed to social demands.